Cost Avoidance of Drug Information Services at the Mental Hospital in Saudi Arabia - Alomi, Yousef Ahmed; Qahtani, Nada Al; Alsulami, Nora; Mashouf Al Qahtani, Mohamed; Almansor, Fahad Abdallah (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the cost-efficiency of drug information services at the mental hospital in Saudi Arabia. Methods: It simulation of cost efficiency of drug information center for four years and a half at a mental hospital in Saudi Arabia. It estimated cost avoidance of running drug information services. Drug information services started from answering inquiries from healthcare providers including a physician, pharmacist, and nurses. The estimated cost of using international Study Model. The value considered were the expected results of drugrelated problems sequel to drug information inquiries; if not existing drug information services and were not answered; starting from Physician visit, additional laboratory test, further treatment, hospital admission, Critical care admission to death stage. The cost estimated for each step. All value used in USA solar currency. Results: The total of drug information inquiries answered with cost avoidance reported was (1084). The total estimated cost avoidance of answered drug information inquiries was (167,623.50) USD with average cost avoidance was (154.63) USD per each inquiry. The most type inquiries estimated cost avoidance was drug dosing (117,316.50) USD followed by the drug of choice (17,960.00) USD and drug interaction (14,024.50) USD. The most estimated cost avoidance by a used references assistant to answer the question and prevent drug-related problem was Drugs.com website (118,683.50) USD, followed by Lexi comp-drug information (100,064.50) USD and prescribing guidelines in psychiatry (18,642.00) USD. The most cost avoidance related to drug information caller was physician (135,787.50) USD, pharmacist (28,624.50) USD and patients (2,342.50) USD. Conclusion: The drug information services are saving a high cost per year despite limited resources. The drug information services with different type need to expand to all departments at a Mental hospital in Riyadh city, Saudi Arabia.
Keywords: Cost avoidance; Drug information; Mental hospital; Ministry of Health; Saudi Arabia